Employment of Set Operations to Improve LMP Assessments Design and Implementation - Malek Khalaf Albezuirat; Rosmaini Ahmad; Muhammad Iqbal Hussain; Falah Mustafa Al-Saraireh; Asia Khalaf Albzeirat (SEISENSE Journal of Management, 2019)
Objective - This paper aims to provide a new mathematical model for the construction of assessment tools for Lean Manufacturing Practices (LMP) through the integration process with the set operations. This study also strives to develop key elements to enhance the effectiveness of LMP assessments and their impact through mathematical interrelationship. Problem - Previous studies have shown a lack of clear mathematical methodology to carry out a rigorous assessment of the LMP effects on the firm’s operational and financial performance. Therefore, this paper tries to address this aspect by developing new equations. Design - The methodology of this study is based on the conversion of the linguistic description (companies, processes, waste, practices) into numerical measurement model by integrating with set theory. Finding - The results show a set of relationships and equations that can be applied to be a fundamental basis for ensuring the effectiveness of the assessment. This paper may contribute to the improvement of LMP’s design and development.